Role of Pedagogical Artistry in Increasing Level of School Tolerance - I. S. Samokhin; N. L. Sokolova; M. G. Sergeyeva; D. O. Romanov (Научный диалог)
The impact of the teacher’s artistry on forming tolerance in the educational environment of the school is considered. Teacher-actor is opposed to the so-called “lessons giver” - the teacher considers himself bound only to teach students, but not to raise them. The analysis is made of modern scientific literature on the pedagogical artistry. It is found that artistic teaching makes students (and to some extent teachers themselves) more tolerant, but this happens indirectly through positive emotions, creating a comfortable learning atmosphere. The link between the style of interaction between teacher and students and pedagogical level of artistry is revealed, the methods conducive to the development of this quality are considered. The study is particularly relevant in connection with the transition to inclusive education, established by the Federal law “On education in Russian Federation.” The novelty of this work is to present the fundamentals of the author’s theoretical-practical course “Acting skills in the practice of school teacher” and the commentaries thereto, prepared by one of the authors of the article - a teacher-practitioner with two higher educations: pedagogical and acting. The authors come to the conclusion that the students of pedagogical specialties should be trained in the artistry not by the Stanislavsky system, but by the system of V. Meyerhold and B. Brecht.